Studi Etnobotani Ritual Erpangir Ku Lau pada Masyarakat Karo di Kecamatan Kabanjahe Kabupaten Karo - Syahfitri, Dinda; Harsono, Tri; Suriani, Cicik; Sari, Wina Dyah Puspita; Handayani, Dina; Pulungan, Ahmad Shafwan S. (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Erpangir Ku Lau ritual is a Karo people's self-purification ritual that has traditionally utilized plants as the main element. This study aims to examine the belief system (cosmos), local knowledge (corpus), and plant utilization practices (praxis) in the Erpangir Ku Lau ritual in Kabanjahe District. The study was conducted in January 2026 in Lau Cimba Village using a qualitative and quantitative descriptive approach through semi-structured interviews with 10 key informants selected by purposive sampling. The results identified 17 species from 11 plant families. The Rutaceae family dominated with 4 species (23.53%), followed by Rosaceae with 3 species (17.65%), and Poaceae with 2 species (11.76%). The most commonly utilized organs were fruits and flowers (29.41%), followed by leaves (23.53%). Shrub habitus dominated with 47.06%. The Karo people view plants as symbolic and spiritually significant, with the kaffir lime (Citrus hystrix D.C.) as a key plant. Plant use reflects holistic local wisdom, combining ecological, chemical, and spiritual aspects. Documenting this traditional knowledge is crucial to prevent its extinction due to modernization.